Optimization of styrofoam as concrete replacement material subjected to compressive strength - Sartika Nisumanti; Yulianti Eka Putri; Tahara; Nofriandi Fitri; Iva Nazila; Fiki Hidayat (Penerbit Universiti Kebangsaan Malaysia, 2024)
Nowadays, the construction sector is developing rapidly, and there is an increase in demand for innovative concrete technology. This is because concrete has many advantages over other building materials. Improving the quality of concrete can be done by providing replacement materials or adding several replacement materials, and one of the alternative materials that can be used is styrofoam. The purpose of this research is to evaluate the effect of styrofoam as high-quality concrete and compare the compressive strength between control concrete by using 1%, 2%, and 3% ratios of styrofoam. The experimental method is applied in this research, experiment was conducted and tested in accordance with SNI 03-6468-2000. The results of the study show that the compressive strength of styrofoam mixed concrete using ratios of 1%, 2%, and 3% obtained 23,30 MPa, 17,34 MPa, and 11,64 MPa. The results showed that Styrofoam replacement was used for K.350 high-strength concrete. It is not recommended for building or bridge construction because the compressive strength test results produced are meagre compared to standard concrete without a mixture of styrofoam. After all, the mass of concrete mixed with styrofoam is lighter than normal concrete so that it can be used for construction with low loads.